Does Managed Care Hurt Health? Evidence from Medicaid Mothers - Aizer, Anna; Currie, Janet; Moretti, Enrico (The Review of Economics and Statistics, 2007)
Most Americans are now in some form of managed care plan that restricts access to services in order to reduce costs. It is difficult to determine whether these restrictions affect health because individuals and firms self-select into managed care. We investigate the effect of managed care using a California law that required some pregnant women on Medicaid to enter managed care. We use a unique longitudinal database of California births in which we observe changes in the regime faced by individual mothers between births. We find that Medicaid managed care reduced the quality of prenatal care and increased low birth weight, prematurity, and neonatal death.